A utilização do Parque Municipal São Francisco de Assis na interpretação ambiental – ano 2022-2023 - Mendes, Silmara Forner Calzavara (2024)
The study titled The Use of São Francisco de Assis Municipal Park in Environmental Interpretation – 2022-2023 aimed to evaluate the role of this urban park as an analytical parameter for Environmental Interpretation, emphasizing the importance of urban parks being seen not only as leisure spaces but also as agents of environmental awareness and education. This is especially relevant in the context of the Sustainable Development Goals (SDGs), such as good health and well-being, quality education, sustainable cities and communities, and life on land. The study highlights the significance of urban parks and explores Conservation Units (CUs), differentiating between Integral Protection Units (IPUs) and Sustainable Use Units (SUUs). With a specific focus on the São Francisco de Assis Municipal Park, located in Assis Chateaubriand, the research demonstrates how these spaces contribute to biodiversity conservation and offer socio-environmental benefits to the community. Furthermore, it discusses the socio-environmental interactions within urban parks and the role of environmental interpretation, illustrating how individuals interact with both natural and built environments and how environmental interpretation fosters a deeper understanding of these interactions and values public spaces. The methodology includes the park's geographic context, physical characteristics, and infrastructure, combined with data collection and analysis. The study utilized documentary and bibliographic surveys, as well as the use of the park as an instrument for environmental interpretation. The research concludes that São Francisco de Assis Municipal Park plays a key role in environmental education and community awareness regarding the importance of environmental conservation. It also underscores the need for policies and practices that promote sustainability in urban spaces, reinforcing the value of parks as places of learning, leisure, and connection with nature, contributing to more sustainable and inclusive cities.